Matthew's dream - Lionni, Leo, 1910- (New York : Knopf, 1991)
A visit to an art museum inspires a young mouse to become a painter.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Publisher's Weekly
4.8
K-3
Keywords: Mice -- Fiction; Artists -- Fiction; Museums -- Fiction; Mice -- Fiction; Artists -- Fiction; Museums -- Fiction